1991
DOI: 10.1172/jci115108
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous blockade of 1,25-dihydroxyvitamin D-receptor binding in New World primate cells.

Abstract: When assessed by 1,25(OH) Clin. Invest. 1991. 87:996-1001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…NWPs are also profoundly resistant to vitamin D. As with glucocorticoids, this appears to be due to impaired signaling via the cognate intracellular receptor, in this case the VDR. Initial studies suggested that the blockade of VDR action in NWPs was due to the elevated levels of a soluble protein that could act as a competitor for binding of 1,25(OH) 2 D (Gacad & Adams 1991, 1992. The purification of this intracellular DBP (IDBP) revealed similarity to the constitutively expressed human heat-shock protein 70 (hsc70) , and also indicated that hsc70 was capable of binding both 25OHD and 1,25(OH) 2 D, as well as gonadal steroids such as estradiol ).…”
Section: Primate Responses To Vitamin D Metabolites: New World Versusmentioning
confidence: 99%
See 1 more Smart Citation
“…NWPs are also profoundly resistant to vitamin D. As with glucocorticoids, this appears to be due to impaired signaling via the cognate intracellular receptor, in this case the VDR. Initial studies suggested that the blockade of VDR action in NWPs was due to the elevated levels of a soluble protein that could act as a competitor for binding of 1,25(OH) 2 D (Gacad & Adams 1991, 1992. The purification of this intracellular DBP (IDBP) revealed similarity to the constitutively expressed human heat-shock protein 70 (hsc70) , and also indicated that hsc70 was capable of binding both 25OHD and 1,25(OH) 2 D, as well as gonadal steroids such as estradiol ).…”
Section: Primate Responses To Vitamin D Metabolites: New World Versusmentioning
confidence: 99%
“…As outlined above, decreased VDR function in NWPs involves diminished nuclear activity of the liganded receptor (Gacad & Adams 1991). This was initially attributed to the elevated levels of IDBPs in NWPs, which were thought to act as decoy-binding sites for 1,25(OH) 2 D .…”
Section: Vdre-binding Proteins (Vdre-bps) and The Regulation Of Vdr-imentioning
confidence: 99%
“…Another proposed microregulator in the vitamin D metabolism/action system is the newly discovered family of hsp70-related intracellular vitamin D-binding proteins. These proteins, initially identified in vitamin D-resistant New World primate cells (52,53), have a high capacity and relatively high affinity (2-20 nM) for 25-hydroxylated vitamin D metabolites (54). Recent work 2 indicates that these proteins have the ability to facilitate hormone action by delivery of 1,25-dihydroxyvitamin D hormone to the nucleus and VDR, which has a higher affinity for hormone than the intracellular vitamin D-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The partially hormone-responsive New World primate ge-3 H. Chen, unpublished data. nus Aotus and the hormone-resistant New World primate genus Callithrix (52) are respective examples of the micro-and macroregulatory phenotype. Because Aotus cells express relatively little mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation